Physiology of Soccer Game : Literature Review - Gaung Perwira Yustika (Universitas Negeri Semarang, 2019)
Abstract Soccer is the most popular sport in the world, with around 270 million people participated in this sport (FIFA, 2015). Soccer attracted attention either sport scientist or government all over the world to promoted the benefit of physical activity and also maintained people's health, including the minorities. (Hammami et al, 2016; Milanovic et al., 2015; Parnell et al., 2016). Besides, this sport can be used to promote the health public in order to prevent chronic diseases cause lack of physical activity (Krustrup et al., 2010). Physiological need of competitive soccer in highest level must have good physical condition in order to give maximal effort in a soccer match (run, hold the ball, passing and shooting). The fitness level optimization is a important aspect in the preparation of a team before joining the competition. There's already many research done, showed the data that a men's soccer professional player can reached 9-14 km of total distance covered in a soccer match. And in the Women's elite soccer game, a player can reached about 8-12 km of total distance covered. (Bloomfeld, et al 2008). But soccer is not always only about physical matter but also mental attributes needed. Research showed that mental fatigue during a soccer game may influenced the technical and physical aspect, made a player can't showed their true ability. This Review article made to show the physiological aspect of the game in soccer, resumed from scientific articles especially from Europe/USA where soccer was more advanced there. And the writer try to compare to the condition in Indonesia where soccer was still under developed there, the data showed that Indonesia was still in the bottom rank of FIFA. The writer hoped that this article can be used to developed sport science and sport medicine in his beloved country.   Keywords : soccer , physiology, physical, energy , mental, sport science.